2011
DOI: 10.2460/ajvr.72.12.1600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a modified acetaminophen absorption test to estimate the abomasal emptying rate in Holstein-Friesian heifers

Abstract: The modified acetaminophen absorption test was a practical, minimally invasive, and reliable method to assess abomasal emptying in cattle. Metoclopramide administered at a dose of 0.1 mg/kg did not increase the abomasal emptying rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
1
6
1
Order By: Relevance
“…tulathromycin in healthy goats was demonstrated by a shorter time to actual T max and model T max , as well as a shorter abomasal emptying half-time (T50), than control. The elimination half time of acetaminophen in this study appeared to be shorter than that reported for cattle (Grochowina and Janus, 2007;Ehsani-Kheradgerdi et al, 2011) and lambs (Sharifi et al, 2009). This result in consistent with a more active metabolism in goats than in cattle or sheep, with goats having a significantly higher activity of UDP-glucuronyltransferase (Short et al, 1988) and higher liver concentrations of cytochrome p-450, NADPH cytochrome c reductase, aldrin epoxidase, aminopyrine Ndemethylase, ethoxycoumarin O-deethylase, microsomal and cytosolic stilbene oxide (epoxide) hydrolase and glutathione s-transferase than sheep and cattle (Wisniewski et al, 1987).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…tulathromycin in healthy goats was demonstrated by a shorter time to actual T max and model T max , as well as a shorter abomasal emptying half-time (T50), than control. The elimination half time of acetaminophen in this study appeared to be shorter than that reported for cattle (Grochowina and Janus, 2007;Ehsani-Kheradgerdi et al, 2011) and lambs (Sharifi et al, 2009). This result in consistent with a more active metabolism in goats than in cattle or sheep, with goats having a significantly higher activity of UDP-glucuronyltransferase (Short et al, 1988) and higher liver concentrations of cytochrome p-450, NADPH cytochrome c reductase, aldrin epoxidase, aminopyrine Ndemethylase, ethoxycoumarin O-deethylase, microsomal and cytosolic stilbene oxide (epoxide) hydrolase and glutathione s-transferase than sheep and cattle (Wisniewski et al, 1987).…”
Section: Discussioncontrasting
confidence: 78%
“…Six weeks later goats received an IM injection of tulathromycin (2.5 mg/kg BW) into the semimembranosus muscle; the duration between tulathromycin injections was to ensure adequate clearance of tulathromycin, based on an estimated mean half-life after IV injection of 4.1 days in these goats (Amer et al, 2012) and 2.5-4.6 days after SC injection in juvenile and market aged goats (Clothier et al, 2011;Young et al, 2011;Romanet et al, 2012). A wash out period of a week was considered adequate for complete clearance of acetaminophen, based on pharmacokinetic studies in cattle (Grochowina and Janus, 2007;Ehsani-Kheradgerdi et al, 2011) and sheep (Sharifi et al, 2009).…”
Section: Experimental Designmentioning
confidence: 99%
“…Ehsani-Kheradgerdi et al . [ 6 ] examined the pharmacokinetics of AAP after its abomasal administration to Holstein-Friesian heifers. They demonstrated that T max was 80 min.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed an impaired acid‐base balance at least in D but to a lesser extent in DORS. The APAT model was used to determine the AER indices that have already been described in previous studies with healthy ruminants and healthy calves (Ehsani‐Kheradgerdi, Sharifi, & Mohri, ; Marshall et al, ; Nouri & Constable, ). Calves are functional monogastric individuals with a biphasic gastric emptying which is best described by the equation of Siegel (Marshall et al, ).…”
Section: Discussionmentioning
confidence: 99%